Phenotypic characterization of SETD3 knockout Drosophila - Tiebe, Marcel; Lutz, Marilena; Teleman, Aurelio A. (PLOS ONE, 2018)
Lysine methylation is a reversible post-translational modification that affects protein function. Lysine methylation is involved in regulating the function of both histone and non-histone proteins, thereby influencing both cellular transcription and the activation of signaling pathways. To date, only a few lysine methyltransferases have been studied in depth. Here, we study the Drosophila homolog of the human lysine methyltransferase SETD3, CG32732/dSETD3. Since mammalian SETD3 is involved in cell proliferation, we tested the effect of dSETD3 on proliferation and growth of Drosophila S2 cells and whole flies. Knockdown of dSETD3 did not alter mTORC1 activity nor proliferation rate of S2 cells. Complete knock-out of dSETD3 in Drosophila flies did not affect their weight, growth rate or fertility. dSETD3 KO flies showed normal responses to starvation and hypoxia. In sum, we could not identify any clear phenotypes for SETD3 knockout animals, indicating that additional work will be required to elucidate the molecular and physiological function of this highly conserved enzyme.
Gesehen am 08.08.2019